2020
DOI: 10.1111/nph.16675
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution of tree hydraulic traits in Amazonian habitats: implications for community assemblage and vulnerability to drought

Abstract: Summary Amazonian droughts are increasing in frequency and severity. However, little is known about how this may influence species‐specific vulnerability to drought across different ecosystem types. We measured 16 functional traits for 16 congeneric species from six families and eight genera restricted to floodplain, swamp, white‐sand or plateau forests of Central Amazonia. We investigated whether habitat distributions can be explained by species hydraulic strategies, and if habitat specialists differ in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 95 publications
5
52
2
Order By: Relevance
“…Our data revealed no significant association between traits and the rainfall‐seasonality gradient modelled by the second axis of the PCA performed on environmental variables (Fig. 3), despite previous works reporting strong evidence that gradient of annual rainfall, and/or seasonality induces a shift in the functional composition of forest tree communities in diverse ecosystems (Laughlin et al 2011, Wieczynski et al 2019, Anderegg et al 2021), including tropical forests where hydraulics traits are greatly influenced by drought (Santiago et al 2018, Gouveia Fontes et al 2020). The lack of rainfall and seasonality signal in our study may likely result from the relatively narrow range of variation in these parameters among plots at the scale of our study (Table 1).…”
Section: Discussionmentioning
confidence: 91%
“…Our data revealed no significant association between traits and the rainfall‐seasonality gradient modelled by the second axis of the PCA performed on environmental variables (Fig. 3), despite previous works reporting strong evidence that gradient of annual rainfall, and/or seasonality induces a shift in the functional composition of forest tree communities in diverse ecosystems (Laughlin et al 2011, Wieczynski et al 2019, Anderegg et al 2021), including tropical forests where hydraulics traits are greatly influenced by drought (Santiago et al 2018, Gouveia Fontes et al 2020). The lack of rainfall and seasonality signal in our study may likely result from the relatively narrow range of variation in these parameters among plots at the scale of our study (Table 1).…”
Section: Discussionmentioning
confidence: 91%
“…This result, in agreement with previous studies (e.g. Cosme et al ., 2017; Fontes et al ., 2020), highlights the role of topographically defined hydrological conditions as environmental filters of species’ taxonomic and functional composition of Amazonian forests, with consequences for forest dynamics. Species with low WD should be those most negatively affected by droughts, as shown elsewhere (Aleixo et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the variation of drought responses as a function of water table depth gradients is important, given that forests over a SWT are widely different from those over a deep water table (DWT), being characterized by higher turnover rates (i.e. more dynamic forests), owing to the combination of acquisitive species traits (Cosme et al ., 2017; Fontes et al ., 2020), shallow roots (Fan et al ., 2017) and soil instability (Ferry et al ., 2010; Cintra et al ., 2013), and that the majority of plots in Amazonian monitoring networks, from which most of our knowledge derives to date, is located in DWT forests, even though almost 40% of the Amazon forests have SWTs (with depths < 5 m; Fan & Miguez‐Macho, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extreme dry hydroclimatic conditions generated (Figure 7) is the most plausible cause for the mortality of E. tenuifolia trees during this period (Figure 5), causing hydraulic failure, carbon starvation, or both, as carbon and water dynamics are interrelated through stomatal conductance and vascular transport (Cailleret et al, 2017; Gessler et al, 2018; Hartmann et al, 2018). Fontes et al (2020) observed a high vulnerability of E. tenuifolia to xylem embolism in the study region, based on measured P 50 values (water potential causing 50% loss of hydraulic conductivity). Dead forests dominated by this species occurred mainly around floodplain lakes and slip‐off slopes of fluvial meanders (Figures 4).…”
Section: Discussionmentioning
confidence: 96%